Broadband high performance laterally diffused metal-oxide-semiconductor power amplifier for mobile two-way radio applications - Kumar, N.; Anand, L. (Inst Engineering Technology-Iet, Michael Faraday House Six Hills Way Stevenage, Hertford Sg1 2ay, England, 2015)
This paper highlights achievement of broadband high performance power amplifier (PA) line up for mobile two-way radio applications. In typical two-way radio applications the input radio-frequency signal to the first PA stage comes directly from the voltage controlled oscillator, with typically 3 dBm power. Owing to high output power requirement (similar to 80 W) of mobile radio applications, up to three PA device stages are normally cascaded (pre-driver, driver and final PA stage). The key point in the design of the PA line up concerns the final stage. Here, this paper introduces a design methodology based on parallel-combined impedance matching technique (from theoretical derivation) enables the designers to develop broadband PA with actual PA device impedance (implementation of new generation laterally diffused metal-oxide-semiconductor device). Experimental results demonstrated output power of similar to 80 W and gain of 45 dB, while preserving efficiency of 55 over the bandwidth from 760 to 870 MHz. According to author's knowledge, this amplifier demonstrated highest efficiency with 13 V DC supply (operating at 80 W) in UHF broadband frequency with high gain operation (more than 45 dB) up to date.